Answer:
y=0
Step-by-step explanation:
Rewrite Evaluate Powers:
3![3^{2y-1}+3^{-1}+2*3^{y}*3^{-1}=1](https://tex.z-dn.net/?f=3%5E%7B2y-1%7D%2B3%5E%7B-1%7D%2B2%2A3%5E%7By%7D%2A3%5E%7B-1%7D%3D1)
Calculate:
![(3^{y})^{2}*\frac{1}{3} +2*3^{y}*\frac{1}{3}=1](https://tex.z-dn.net/?f=%283%5E%7By%7D%29%5E%7B2%7D%2A%5Cfrac%7B1%7D%7B3%7D%20%2B2%2A3%5E%7By%7D%2A%5Cfrac%7B1%7D%7B3%7D%3D1)
Solve using substitution:
![t=3^{y}](https://tex.z-dn.net/?f=t%3D3%5E%7By%7D)
Solve the equation for t:
t=-3
t=1
Substitute back to t=3^y
3^y=-3
3^y=1
y∉R
![3^{y}=1](https://tex.z-dn.net/?f=3%5E%7By%7D%3D1)
y=0
Answer:
P(X<=2) = 0.9736
Step-by-step explanation: Please find the attached file for the solution
Step-by-step explanation:
- (1/7)³=1³/7³=1/343
- 2⁵=32
- 1.4²=1,4×1,4=1,96
I will mark brainlist please help
Story : A Dog’s Tale by Mark Twain
4. Read this sentence from the selection.
“Whenever she heard a large word she said it over to herself many times, and so was able to keep it until there was a dogmatic gathering in the neighborhood.”
In this sentence the word dogmatic is used as —
• an insightful simile
• a descriptive metaphor
• a humorous play on words
• an illuminating allusion
5. In the last paragraph the narrator says his mother would “fetch out a long word.” The connotations of the word fetch remind the reader that the narrator’s mother —
• is well educated
• is a dog
• knows lots of big words
• likes to show off
8. What is ironic about the author’s mother showing off with her knowledge of the word unintellectual?
• Her child knew she didn’t understand the word correctly.
• The strangers all already knew the meaning of the word.
• As any intellectual would know, the word should be “nonintellectual.”
• She did not know any synonyms for the word.
9. Which type of person is most like the author’s mother?
• A high-performing student with an excellent memory for words
• A very verbal person who always has a quick answer that sounds good
• A dishonest person who tells lies on a regular basis
• A person who likes dogs a lot and works at a veterinary clinic
Hello from MrBillDoesMath!
Answer:
The fourth choice, b = +\- sqrt( sg + a^2)
Discussion:
s = (b^2 - a^2)/g => multiply both sides by "g"
sg = b^2 - a^2 => add a^2 to both sides
sg + a^2 = b^2 => take the square root of each side
b = +\- sqrt( sg + a^2)
which is the fourth choice.
Thank you,
MrB